2018
DOI: 10.1155/2018/8784958
|View full text |Cite
|
Sign up to set email alerts
|

Oophoropexy for Recurrent Ovarian Torsion

Abstract: A 31-year-old nulliparous patient presents with a three-day history of right sided colicky abdominal pain and associated nausea. This patient has previously presented twice with right sided ovarian torsion with the background of polycystic ovaries in the last two consecutive years. Blood tests were normal. Due to previous history, there was a high index of clinical suspicion that this may be a further torsion. Therefore, the patient was taken to theatre for a diagnostic laparoscopy and a further right sided ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 14 publications
0
18
0
Order By: Relevance
“…Typically, the infundibulopelvic ligament of the right ovary is longer in most patients, and the sigmoid colon decreases the mobility of the left ovary. Therefore, the possibility of torsion of the right ovary is more likely than torsion of the left ovary [11]. In our case, however, all torsion episodes occurred in the left ovary.…”
Section: Discussionmentioning
confidence: 70%
“…Typically, the infundibulopelvic ligament of the right ovary is longer in most patients, and the sigmoid colon decreases the mobility of the left ovary. Therefore, the possibility of torsion of the right ovary is more likely than torsion of the left ovary [11]. In our case, however, all torsion episodes occurred in the left ovary.…”
Section: Discussionmentioning
confidence: 70%
“…Although preventing recurrent adnexal torsion is a clinically important management strategy, indications and approaches remain non-standardized due to the rarity of this condition. There have been several reports on the utility of preventive surgical techniques for recurrent torsions; oophoropexy is one of these techniques, and it involves fixation of the ovary to the pelvic sidewall, to the lateral round ligaments, or to the uterosacral ligament [[17], [18], [19], [20]]. Djavadian et al noted that detorsion should be performed in the first step, but in case of recurrence, they recommend an oophoropexy to avoid reappearance of the torsion [18].…”
Section: Discussionmentioning
confidence: 99%
“…Oophoropexy has been described as a preventive intervention to decrease the risk of recurrent torsion. Various techniques have been described, including plication of the utero-ovarian ligament, suturing the ovary to the round ligament or the posterior uterus, or pelvic sidewall [52][53][54]. Small studies have shown success with fertility and normal appearance of ovaries on follow-up ultrasound, but long-term effects of oophoropexy on recurrence rates and fertility are not known [52].…”
Section: Treatmentmentioning
confidence: 99%